Career Planning and Career Management: Case on Workforce in Makassar - Tikson, Shinta Dewi Sugiharti; Sahas, Nadya Septiani; -, Sri Ulfa; -, Nurfadillah (Faculty of Economics and Business, Hasanuddin University, 2021)
Every employee has a career goal he or she wants to achieve. In achieving his or her career, an employee will explore all available opportunities. Career planning is an effort made by individuals in setting goals or achieving desired career goals. This includes activities such as analyzing the abilities possessed, interest in work, values, to identify goals that need to be achieved in supporting the desired career. Looking at the current reality, many companies are experiencing changes caused by the coronavirus pandemic. This problem is felt not only by companies but also by employees because it can hinder their careers. This research is expected to provide insights on individual career planning and the role of organization in career management. This study shows there is a significant relationship between career planning and career management.